Características produtivas e valor nutritivo do capim-Tanzânia fertilizado com nitrogênio, sob pastejo - Iwamoto, Bruno Shigueo (2010)
It is undeniable that Brazil has favorable conditions for livestock production based on pastures, that represent one of the major ecosystems and they are considered the base for the livestock and of extreme importance to the national economy, since to the world market the breeding of grazing cattle is characterized by lower production cost. The research is a means of information to help the producer to improve the conditions management and animal production based on pastures. Within this context, the purpose of this study was to evaluate the production, morphology composition, chemistry composition, morphogenesis and tillering features in grazed of Tanzania grass (Panicum maximum cv. Tanzania) fertilized with nitrogen levels under intermittent grazing. The experiment was conducted at the Experimental Farm of Iguatemi - UEM, from April 2008 to September 2009. It was used a randomized block design with split plot design with four replicates. The treatments were: N1 = zero, N2 = 150, N3 = 300 and N4 = 450 kg of nitrogen.ha-1 and the seasons of the year: fall, winter, spring and summer of 2008 and autumn and winter of 2009.The highest accumulation of dry matter per cutting was obtained at the highest dose of N in spring and summer. The fertilizer N, especially in higher quantities, provides the highest percentages of leaf and stem + sheath. However, with reduction in the percentage of dead material. Regardless of N dose, higher percentages of leaf and less of dead material were obtained in spring and summer. The highest percentage of stem + sheath was obtained mainly in summer and autumn of 2008/09. The N, improved the quality of Tanzania grass with increased CP and digestibility. Spring and summer contribute to the increase in the digestibility as well in the NDF content. In general, summer was when there was the best forage quality, with more evidence in the largest doses of N (300 and 450 kg). In autumn and winter of 2009, the largest LFL were obtained at the highest dose of N (450 kg). At the same seasons, there was effect of N in the NLL. Both LAR and LER responded to N showing higher rates in the highest N doses (300 and 450 kg) and in summer followed by spring contributing to the fall of phyllochron and DLF. In summer it was observed higher LSR independent of N dose evaluated. As for the SER, higher values were obtained in summer and autumn of 2008/09. In spring, summer and autumn/09, the major and minor SER were obtained at higher (450 kg) and lower dose of N (0 kg), respectively. Regardless of the seasons, the highest densities of tillers were obtained at a dose of 300 kg of N, and, except to the treatment without fertilization, higher densities were obtained in summer. Higher densities were obtained in the winter of 2008 when compared to winter of 2009. The highest rates of onset and death of tillers were obtained at higher N rates (300 and 450) and in summer followed by spring. The nitrogen fertilization associated with the most favorable seasons of pasture growth (spring and summer) contributes to the further growth of Tanzania grass to accelerate the morphogenic and tillering pace. High levels of nitrogen doses associated with shorter intervals of grazing encourage greater production and improvement in the nutritional value of Tanzania grass under stocking.